Cytotoxicity of Dental Adhesives In Vitro - Koulaouzidou, Elisabeth A.; Helvatjoglu-Antoniades, Maria; Palaghias, George; Karanika-Kouma, Artemis; Antoniades, Dimitrios (European Journal of Dentistry, 2009)
Objectives: The purpose of this study was to evaluate the cytotoxic effect of six dental adhesives (Admira Bond, Clearfil Liner Bond 2V, ED Primer II, Fuji Bond LC, Gluma Comfort Bond, and NanoBond) applied to cell cultures.Methods: The experiments were performed on two cell lines, rat pulp cells (RPC-C2A) and human lung fibroblasts (MRC5). Samples of the adhesives were light-cured and placed in culture medium for 24 hours. The extraction media was applied on the RPC-C2A and the MRC5 cells. Complete medium was used as a control. Cytotoxicity was evaluated with a modified sulforhodamine B (SRB) assay after 24 hours of exposure.Results: The cell survival of RPC-C2A cells exposed to Fuji Bond LC, NanoBond, Clearfil Liner Bond 2V, ED Primer II, Admira Bond and Gluma Comfort Bond was 73%, 67%, 50%, 20%, 18% and 5% respectively, relative to the cell survival with the control medium. In the MRC5 cell line, the relative survival was 98%, 80%, 72%, 41%, 19% and 7% after exposure to NanoBond, Fuji Bond LC, Clearfil Liner Bond 2V, ED Primer II, Admira Bond and Gluma Comfort Bond, respectively.Conclusions: Different types of dental adhesives showed different cytotoxic effects on cells in vitro. The self-etch adhesives were superior in terms of cytotoxicity. The different cytotoxic effects of dental adhesives should be considered when selecting an appropriate adhesive for operative restorations. (Eur J Dent 2009;3:3-9)
Keywords: Cell culture; Cytotoxicity; Dental adhesives; In vitro; SRB-assay